The importance of cuisine as a nutritional strategy for children from 6 months to 2 years (Research, Society and Development, 2024)
The present study aims to demonstrate the relevance of cooking as a nutritional strategy in the preparation of infant food. The work refers to a qualitative and experimental research, with discernment to the objective as explanatory, exploratory and descriptive, where it was elaborated in two stages. The first stage consisted of a data collection through a bibliographic review. The second stage consisted of making the children's e-book. Eating based on healthy habits is of paramount importance in the first two years of life and should continue until childhood. According to data from the Ministry of Health, in the world, there are a total of 124 million obese children and adolescents, and in Brazil, 9.4% are girls and 12.4% are boys. One study analyzed the effect of an interference in nutritional education with children between 2 and 6 years old. After the action, carried out with freestyle drawings, 76% of the children were able to understand the beneficial effects that the consumption of healthy foods will bring to their health. Therefore, the importance of cooking as a nutritional strategy in the preparation of children's food is emphasized, the way in which food is prepared and served to children contributes to the development of eating habits that encourage acceptance and the search for more nutritious and healthy foods.